2013
DOI: 10.2147/opth.s54511
|View full text |Cite
|
Sign up to set email alerts
|

Topical rebamipide improves lid wiper epitheliopathy

Abstract: Administration of topical rebamipide increases the mucin level of tear film and improves the ocular surface in short break-up time type of dry eye. Lid wiper epitheliopathy (LWE) is a disorder of the marginal conjunctiva of the upper eyelid with dry eye symptoms. LWE may be related to mechanical forces during blinking resulting in inflammation of the ocular surface. Rebamipide also has various anti-inflammatory effects. In this report, we tried treatment with topical rebamipide for two cases of LWE. One case h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Treatment of severe LWE would likely necessitate the targeting of a different disease pathway in LWE, such as the use of topical mucin secretagogues to increase mucin production in the ocular surface. 55,56 Although greater tear film instability is noted with contact lens wear, it only plays a minor role in why a higher prevalence of LWE was observed in contact lens wearers; this conjecture is supported by the small effect size of LWE by FTBUT observed in our statistical model. Instead, it is the higher coefficient of friction (CoF) in contact lens compared to an ocular surface without contact lens that may be a major contributor for the difference in LWE.…”
Section: 13supporting
confidence: 58%
“…Treatment of severe LWE would likely necessitate the targeting of a different disease pathway in LWE, such as the use of topical mucin secretagogues to increase mucin production in the ocular surface. 55,56 Although greater tear film instability is noted with contact lens wear, it only plays a minor role in why a higher prevalence of LWE was observed in contact lens wearers; this conjecture is supported by the small effect size of LWE by FTBUT observed in our statistical model. Instead, it is the higher coefficient of friction (CoF) in contact lens compared to an ocular surface without contact lens that may be a major contributor for the difference in LWE.…”
Section: 13supporting
confidence: 58%
“…Goblet cells contribute to the maintenance of the normal precorneal tear film (3) and also the internal lubrication system for reduction of friction between the lid margin and the globe (2). Clinically, goblet cell damage in the lid wiper may induce deterioration in mucin secretion and friction, which lead to several ocular surface disorders such as dry eye and lid wiper epitheliopathy (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that topical administration of rebamipide, an antiulcer agent, increases the mucin level of the tear film and improves the conditions of the ocular surface in dry eyes (6) and lid wiper epitheliopathy (4). Previous studies have reported that rebamipide facilitates the secretion of mucin.…”
Section: Introductionmentioning
confidence: 99%
“…No specific study was found for rebamipide use in thyroid eye disease with dry eye disease after search of Google scholar and Pubmed. But studies were done on the effects of rebamipide ophthalmic suspension on superior limbic keratopathy (SLK), 33 lagophthalmos, 34 lid wiper epitheliopathy 35 and persistent corneal erosion. 36 Takahashi et al reported that thyroid eye disease patients with SLK after using topical rebamipide showed an improvement and complete disappearance of SLK in 84.8% of patients after treatment.…”
Section: Discussionmentioning
confidence: 99%